Effectiveness of Environmental Management waiting for Physician for Hypertension Patients at Outpatient Department in Song Hospital, Song District, Phare Province - ประสิทธิผลของการจัดสิ่งแวดล้อมให้ผู้รับบริการที่มีภาวะความดันโลหิตสูงขณะรอตรวจที่แผนกผู้ป่วยนอกโรงพยาบาลสอง อำเภอสอง จังหวัดแพร่ - Khowrat, Jeerawat; Boonpan, Jariya ((PMJCS) Phrae Medical Journal and Clinical Sciences, 2018)
Background: Hypertension is one of the most serious problem in public health system. Obviously, it can lead to the complications such as cardiac arrhythmia, acute stroke, acute myocardial infarction, and sudden cardiac arrest. Preventing these events during waiting for physical examination and diagnosis by physician, we would like to reduce the high blood pressure patients serviced in the outpatient department especially the anxious or nervous patients by the management of environment. Objectives: To studied effects of the environment management by using relaxed and peaceful setting to calm down the anxious or nervous patient. Study design: An interrupted time design that patients was divided in two groups controlled by the time of their blood pressure management. The patients must had both their systolic blood pressure from 160 mmHg. to 190 mmHg. and their diastolic blood pressure from 100 mmHg. to 110 mmHg. About 180 patients were recruited the study every other week that 82 patients took a rest in the new environment as the intervention group, 98 patients took a rest in the old environment during waiting for physical examination and diagnosis as the control group. By using the vital signs, the first time blood pressure, 15 minutes after taking a rest, and the time before discharge from the environment, the patients were monitored with gently and safety. Results: The systolic blood pressure reduction in the intervention group was statistically significant more than the control group (p=0.001). On the other hand, there was no significance in diastolic blood pressure reduction between the separate two groups. Conclusion: The environmental management for the outpatient cases with hypertension could reduce the systolic blood pressure. Keywords: Environmental Management, Pulse, Blood pressure, Hypertension